Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 62. Beitrag. Bibliographie zur entomologischen Erforschung Albaniens. II. Teil. - Königsmann, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1967)
This is the second part of a bibliography on Albania. It has 221 entries of publications original references to finds in Albania or new descriptions from Albania. All papers published so far in evaluation of the expedition to Albania by Deutsches Entomogisches Institut are included. If necessary, a short abstract is added to the entry.